Bridges and Barriers: Adolescent Perceptions of Student–Teacher Relationships. (January 2013) - McHugh, Rebecca Munnell; Horner, Christy Galletta; Colditz, Jason B.; Wallace, Tanner LeBaron
In urban secondary schools where underpreparation and dropping out are real world concerns, students understand that their relationships with teachers affect their learning. Using descriptive coding and thematic analysis of focus group data, we explore adolescents' perceptions of the bridges that foster and the barriers that inhibit supportive relationships with teachers, and the boundary expectations that function as both. The characteristics of supportive student–teacher relationships identified by youth participants suggest a number of teacher practices capable of meeting adolescents' developmental needs and, as such, are likely to positively influence adolescents' developmental and academic trajectories.